2012
DOI: 10.1002/ep.11606
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐catalyzed esterification of naphthenic acids

Abstract: The reclamation of mining operation tailings water is of major concern to the oil sands industry. Naphthenic acids (NAs) are recognized as a major toxic component in tailings water. The acid‐catalyzed esterification of commercially prepared NAs to biodiesel was performed as a test case for the utilization of these toxic compounds. In a series of batch acid‐catalyzed esterification reactions, the influence of reaction temperature, catalyst type, catalyst concentration, and methanol to oil ratio on the esterific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It is found that the bands around 2923, 2854, 1083, and 1068 cm –1 assigned to EG are weakened significantly, suggesting the consumption of EG in the interlayer. In addition, the bands around 1368 and 1556 cm –1 are observed, which can be attributed to the ν 3 mode of interlayer CO 3 . For NiAl-4-RC, a band around 1640 cm –1 is observed, which can be assigned to the bending vibration of water in the interlayer. In fact, this band may partly overlap with the band around 1556 cm –1 to form a shoulder in other NiAl- x -RC samples.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is found that the bands around 2923, 2854, 1083, and 1068 cm –1 assigned to EG are weakened significantly, suggesting the consumption of EG in the interlayer. In addition, the bands around 1368 and 1556 cm –1 are observed, which can be attributed to the ν 3 mode of interlayer CO 3 . For NiAl-4-RC, a band around 1640 cm –1 is observed, which can be assigned to the bending vibration of water in the interlayer. In fact, this band may partly overlap with the band around 1556 cm –1 to form a shoulder in other NiAl- x -RC samples.…”
Section: Resultsmentioning
confidence: 94%
“…The crude oil with a total acid number (TAN) higher than 0.5 mg KOH/g is regarded as high acid oil, which usually leads to severe corrosion in pipelines and refinery equipment . The acids in crude oil are mainly naphthenic acids with five- or six-membered rings and one carboxyl group. , Among the various deacidification methods, the esterification between naphthenic acids and alcohols has been proved to be an attractive technique due to its mild reaction conditions, high yield, and few negative effects on the quality of crude oil. …”
Section: Introductionmentioning
confidence: 99%
“…The acid‐catalyzed esterification of commercially prepared naphthenic acid to biodiesel was performed. Sulfuric acid was identified as a preferred catalyst for the esterification compared with p ‐toluene sulfonic acid .…”
Section: Influence Of Variablesmentioning
confidence: 99%
“…Since feedstock costs account for a large percent of the direct biodiesel production costs, use of waste cooking oils or inedible and low cost oils (ex: camelina sativa) can reduce the biodiesel production costs [41][42][43][44]. Although, the kinetics of many virgin feedstock (oils) were reported by several researchers, kinetics of waste cooking oils using ultrasonic method, and base catalyzed reaction has not been reported thus far.…”
Section: Introductionmentioning
confidence: 99%